Spatial and temporal variability of glaciers and rock glaciers in the central italian alps (Lombardy region) - SCOTTI, RICCARDO (Università degli Studi di Milano-Bicocca, 2013)
This study aims to investigate the cryosphere of the Lombardy region (Central Italian Alps) by compiling and analysing glacier, rock glacier, and protalus rampart inventories. To this purpose, I have employed remote sensing techniques and in-situ measurements for delineating the contemporary and historical extent of glaciers and contemporary extent of rock glaciers and protalus ramparts. In order to better identify and highlight the response of the regional cryosphere to climate change, the LIA maximum extent has been reconstructed for nine selected glaciers and their fluctuations since then have been discussed and analyzed in relation to temperature and precipitation recorded at ground weather stations. The main objectives of this doctoral dissertation are to: compile glacier, rock glacier and protalus rampart regional inventory for the Central Italian Alps (Lombardy region) exploitable for investigations about permafrost distribution; elucidate the linkages between the occurrence of periglacial landforms (rock glaciers and protalus ramparts) and local litho-topographic attributes; examine the variability of periglacial activity in relation to terrain elevation and mean annual precipitation; gain new insights about the impact of the Pleistocene-Holocene climatic transition on the periglacial domain within the study area; examine the linkages between glaciers location, glaciers attributes (e.g., size, aspect, ELA0) and mean annual precipitation; analyze the relations between glaciers location, size, aspect, ELA0 and areal variations since 1991; analyze post-LIA (1860) glacier fluctuations for nine selected glaciers from different sub-regions of the central Italian Alps; investigate glacier sensitivity to climate change (i.e., precipitation and temperature).